Atomistic study of GaSe/Ge(111) interface formed through van der Waals epitaxy. (2nd October 2018) - Yonezawa, Takahiro; Murakami, Tatsuya; Higashimine, Koichi; Fleurence, Antoine; Oshima, Yoshifumi; Yamada‐Takamura, Yukiko
Abstract : Layered materials can be grown on various substrates through van der Waals epitaxy (vdWE) regardless of lattice mismatch. The atomistic study of the film‐substrate interface in vdWE is becoming increasingly important due to their expected applications as two‐dimensional (2D) materials. In this contribution, we have grown GaSe thin films on Ge(111) substrates by molecular beam epitaxy and studied the GaSe/Ge(111) interface using high‐angle annular dark‐field scanning transmission electron microscopy (HAADF‐STEM). Cross‐sectional HAADF‐STEM observations revealed that the grown layers adopt predominantly the expected wurtzite‐like structure and stacking, but layers with zinc‐blende‐like structure, similar to Ga2 Se3 but apparently different, and other layer stacking sequences, exist locally near the film‐substrate interface. These results demonstrate that even in vdWE, structural changes can occur in the grown layers adjacent to the substrate, highlighting the importance of such interface for synthesizing and applying ultimately thin 2D materials.